Tratamiento odontológico en paciente de 10 años con paladar fisurado atendida en la clínica de la universidad Antonio Nariño sede Neiva – Huila, 2023 - 1: reporte de un caso (2023)
Objective: To analyze, through a case report, the pediatric dental approach of a 10-year-old patient with cleft palate treated at the clinic of the Antonio Nariño University, Neiva - Huila, 2023 - 1 Starting from an active case in the Dental Clinic of the Antonio Nariño University period 2023 - 1; With the help of tangible tools such as clinical history, x-rays and study models, the management of the 10-year-old patient with a diagnosis of cleft palate within the practice of pediatric dentistry is evident. Having as a reference that throughout dental care at the university there is a low prevalence of care for patients with this condition and the lack of information about the management required by congenital defects such as cleft palate.